DESAIN INFOGRAFIS PEMBELAJARAN BERBASIS MICROSOFT EXCEL PADA DINAS KOMINFO PROPINSI JAMBI - -, mulyadi; Megawaty, Merti; Zahra, Nabila (LP2M Universitas Nurdin Hamzah, 2024)
The digital era demands that all forms of activities be carried out quickly, effectively and efficiently, using the latest technology. In the current era of technological reform 4.0, various information can be obtained in a short time via smart devices with certain applications, one of which is an application for calculating learning values and infographic processing. Solving the problem of spending value and infographics on goods and services data requires effort and a calculation process. thorough and complex. In this article the author describes an application for solving the problem of calculating learning values and infographics at the Dinas Kominfo Propinsi Jambi Service effectively, quickly and accurately using Microsoft Excel software.